Peaceful Islamist mobilization in the muslim world : what went right - Hwang, Julie Chernov; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2009)
In Peaceful Islamist Mobilization in the Muslim World: What Went Right , Julie Chernov Hwang presents a compelling and innovative new theory and framework for examining the variation in Islamist mobilization strategies in Muslim Asia and the Middle East.
Keywords: Religion; Religion and sociology; Ethnology -- Asia; Asia -- Politics and government; Middle East -- Politics and government; Political philosophy; Social sciences -- Philosophy